2021
DOI: 10.3389/fmolb.2021.676065
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Cycled Enzymatic DNA Amplification and Surface-Enhanced Raman Scattering for Sensitive Detection of Circulating Tumor DNA

Abstract: Circulating tumor DNA (ctDNA) represents an emerging biomarker of liquid biopsies for the development of precision cancer diagnostics and therapeutics. However, sensitive detection of ctDNA remains challenging, due to their short half-life and low concentrations in blood samples. In this study, we report a new method to address this challenge by integrating cycled enzymatic DNA amplification technique and Au nanoparticle@silicon-assisted surface-enhanced Raman scattering (SERS) technique. We have demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The content of single-base mutated ctDNA sequences increased in diffuse intrinsic pontine gliomas (DIPGs). Miao et al ( 60 ) reported a method by combining cyclic enzyme DNA amplification technology and gold nanoparticles@silicon (AuNPs@Si) assisted SERS technique, as shown in Figure 8 . They designed an oligonucleotide probe folded into a stem ring hairpin, labeled with a cyanine dye (Cy5) at the 5′ end.…”
Section: Application Of Responsive Sers Probes In Biomedical Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of single-base mutated ctDNA sequences increased in diffuse intrinsic pontine gliomas (DIPGs). Miao et al ( 60 ) reported a method by combining cyclic enzyme DNA amplification technology and gold nanoparticles@silicon (AuNPs@Si) assisted SERS technique, as shown in Figure 8 . They designed an oligonucleotide probe folded into a stem ring hairpin, labeled with a cyanine dye (Cy5) at the 5′ end.…”
Section: Application Of Responsive Sers Probes In Biomedical Fieldsmentioning
confidence: 99%
“…(C) SERS spectra of testing Cy5 collected from 50 random spots on the AuNPs@Si substrate in a single assay. (D) Averaged SERS intensities at three peaks from 50 random spots, respectively ( 60 ). Copyright 2021 Frontiers Media SA.…”
Section: Application Of Responsive Sers Probes In Biomedical Fieldsmentioning
confidence: 99%
“…DNA nanotechnology takes advantage of DNA structures and functions that have not yet been used in the natural world [ 1 , 2 ], which makes DNA not only function as a genetic information carrier [ 3 , 4 , 5 ], but also act as a role of programmable material [ 6 , 7 ]. Owing to the distinct advantages of programmability and predictability, DNA molecules have been used for fabricating two- or three-dimensional nanostructures by a precise sequence design [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%